Fatigue behaviour of slender corrugated webs subjected to plate breathing. (May 2019) - Wang, Z.Y.; Zhang, T.; Chen, Y.; Yuan, F.; Zhou, X.F.; Liu, Z.F.
Highlights: Fatigue crack modes of corrugated webs in plate breathing are evaluated. Fatigue design formulae are proposed for breathing corrugated webs. FE models allowing for combined shear and tearing are developed for plate buckling. Proposed fatigue life prediction of breathing corrugated webs is shown to be desired. Abstract: This paper presents a study on the fatigue behaviour of slender corrugated webs subjected to plate breathing. It outlines a fatigue test of nine test girders with buckling in interactive buckling manner of the corrugated webs. Characteristic fatigue crack propagation manners and fatigue endurances of the corrugated webs are analyzed. Finite element models considering crack propagation details and out-of-plane deflection have been developed to investigate the stress intensity factor under shear and its combined modes. Proposed theoretical prediction allowing for the interacted shear and tearing fracture modes is confirmed with good degree of accuracy and its further improvement is also discussed.